Glutathione S-transferases in elasmobranch liver. Molecular heterogeneity, catalytic and binding properties, and purification - Sugiyama, Yuichi (1981)
In order to gain insight into the phylogeny and physiological significance of organic-anion-binding proteins in the liver, the hepatic glutathione S-transferases of rat and a typical elasmobranch, the thorny-back shark (Platyrhinoides triseriata), were compared with respect to both glutathione S-transferase activites and organic-anion-binding properties. On gel filtration (Sephadex G-75, Superfine grade) of rat cytosol, the elution volumes of enzyme activities with 1-chloro-2,4-dinitrobenzene and p-nitrobenzyl chloride as substrates were identical (rat Y-fractions; M(r) 45000). In contrast, two peaks of enzyme activity for 1-chloro-2,4-dinitrobenzene with elution volumes corresponding to M(r) 52000 (PLAT Y(1)) and M(r) 45000 (PLAT Y(2)) were detected on gel filtration of P. triseriata cytosol. Only fraction PLAT Y(2) had enzyme activity with p-nitrobenzyl chloride. Enzyme kinetic studies showed that rat Y-fraction had higher affinities for both 1-chloro-2,4-dinitrobenzene and glutathione than PLAT Y(1)- and PLAT Y(2)-fractions. The two forms of P. triseriata glutathione S-transferases differed greatly in affinity for glutathione. At a glutathione concentration that we found to be physiological in P. triseriata, PLAT Y(2) accounted for approx. 70% of the total glutathione S-transferase activity with 1-chloro-2,4-dinitrobenzene. Binding studies revealed that PLAT Y(1) and PLAT Y(2) fractions had much lower affinities for sulphobromophthalein and bilirubin than rat Y-fraction. In contrast, binding affinities of PLAT Y(1) and PLAT Y(2) for Rose Bengal and 1-anilino-8-naphthalenesulphonate were comparable with that of rat Y-fraction. Inhibitory kinetics suggested that sulphobromophthalein and Rose Bengal were non-competitive inhibitors of glutathione S-transferase activities when 1-chloro-2,4-dinitrobenzene was used as substrate for both PLAT Y(1) and PLAT Y(2). The major glutathione S-transferase from the PLAT Y(2) fraction was purified 81-fold by sequential chromatography on Sephadex G-75, DEAE-Sephadex and hydroxyapatite, and consisted of two identical subunits with pI7.7. The highly enriched Y(2)-fraction retained high affinity binding of Rose Bengal and 1-anilino-8-naphthalenesulphonate.